SAE Technical Paper Series 2018
DOI: 10.4271/2018-01-1015
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Prediction for Optimal Fuel Economy Vehicle Control

Abstract: V ehicle control using prediction based optimal energy management has been demonstrated to achieve better fuel economy resulting in economic, environmental, and societal benefits. However, research focusing on prediction derivation for use in optimal energy management is limited despite the existence of hundreds of optimal energy management research papers published in the last decade. In this work, multiple data sources are used as inputs to derive a prediction for use in optimal energy management. Data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Therefore, the process of perception, planning, and vehicle actuation uses second-by-second feedback with the Optimal EMS computed for 15-second predictions which has been shown in previous research to be an effective prediction window for achieving FE improvements [26]. Plots of the output of this particular algorithm are shown in another research paper from the authors [34]. Figure 12 shows the overview of the planning subsystem model.…”
Section: Planning Subsystem Model This Vehicle Operationmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the process of perception, planning, and vehicle actuation uses second-by-second feedback with the Optimal EMS computed for 15-second predictions which has been shown in previous research to be an effective prediction window for achieving FE improvements [26]. Plots of the output of this particular algorithm are shown in another research paper from the authors [34]. Figure 12 shows the overview of the planning subsystem model.…”
Section: Planning Subsystem Model This Vehicle Operationmentioning
confidence: 96%
“…Details of an Optimal EMS derivation and implementation can be found in numerous articles [25,34,35]. An overall system-level viewpoint of an Optimal EMS implementation developed in previous research [27] is shown in Figure 10.…”
Section: Optimal Energy Management System Derivationmentioning
confidence: 99%
“…In 2018, OSU announced two research results, one is of the performance improvement of coasting in N gear [18] ,and the other is about the nonlinear simulation of predictive cruise control [19] . By modifying 2010 Prius, CSU(Colorado State University) inquired several research topics, including the speed prediction by V2V-based technology vehicle to improve HEV fuel economy [20] , ADAS to improve vehicle fuel economy [21] , and improve the accuracy of prediction on fuel economy by control optimize [22] .…”
Section: Researches and Activities In Usmentioning
confidence: 99%
“…In 2015, the advantages of ANN prediction were shown in [21,22]. In 2017 and 2018, a series of studies [15,17,29,30] experimented with different data streams to optimize prediction with a shallow ANN. In 2019, more modern machine learning techniques were introduced into the field in [31] where reinforcement learning was used along with traffic data to train an ANN to produce optimal controls for a power-split hybrid.…”
mentioning
confidence: 99%